Comparative study of different gel bases with herbal and synthetic active substance - Hosszú, Zsolt; Sharafi, Shahab; Emadzadeh, Sahand; Kósa, Dóra; Haimhoffer, Ádám; Nacsa, Fruzsina; Pető, Ágota (De Remediis, 2025)
This study compares two gel bases in which either natural or synthetic active substances are incorporated: Philadelphus coronarius flower extract and BGP-15. The preparations were evaluated for texture analysis, in vitro drug release and pH characteristics. Gels were formulated using Carbopol 940 or hydroxypropyl methylcellulose (HPMC) as gelling agents. Texture analysis revealed comparable mechanical properties with slight increases in firmness upon incorporation of active substances. In vitro release studies demonstrated rapid early release for both gel bases, with Philadelphus coronarius reaching approximately 27% release at 180 minutes and BGP-15 achieving ~26% release. The findings support the dermal applicability of both agents and highlight their potential roles in natural and synthetic therapeutic skin preparations.